EVALUATION OF GYMNASTS LASSALISTAS OF ARTISTIC GYMNASTICS IN MANAUS (Fiep Bulletin - online, 2014)
This paper presents a study evaluating gymnasts of Lassalista's club held at La Salle (Manaus - Amazonas). The main objective of this research was to determine which gymnasts must compete on a National Artistic Gymnastics Tournament to be held in November 2013 from an assessment by the tests presented by Bulgarians Nedialkova, Soares & Barros (2006), physical tests presented by Machado (2010) and the mandatory elements required by National Tournament. Among the most relevant observations can highlight the difficulties in training, and team effort in participating in national competitions. Thus we can see that even with the difficulties presented the Amazonas is progressing in Artistic Gymnastics.
Keywords: Artistic gymnastic; Physical Evaluation; Physical training.